Highly Active Superbulky Alkaline Earth Metal Amide Catalysts for Hydrogenation of Challenging Alkenes and Aromatic Rings - Martin, Johannes; Knüpfer, Christian; Eyselein, Jonathan; Färber, Christian; Grams, Samuel; Langer, Jens; Thum, Katharina; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Two series of bulky alkaline earth (Ae) metal amide complexes have been prepared: Ae[N(TRIP)2]2 (1-Ae) and Ae[N(TRIP)(DIPP)]2 (2-Ae) (Ae=Mg, Ca, Sr, Ba; TRIP=SiiPr3, DIPP=2,6-diisopropylphenyl). While monomeric 1-Ca was already known, the new complexes have been structurally characterized. Monomers 1-Ae are highly linear while the monomers 2-Ae are slightly bent. The bulkier amide complexes 1-Ae are by far the most active catalysts in alkene hydrogenation with activities increasing from Mg to Ba. Catalyst 1-Ba can reduce internal alkenes like cyclohexene or 3-hexene and highly challenging substrates like 1-Me-cyclohexene or tetraphenylethylene. It is also active in arene hydrogenation reducing anthracene and naphthalene (even when substituted with an alkyl) as well as biphenyl. Benzene could be reduced to cyclohexane but full conversion was not reached. The first step in catalytic hydrogenation is formation of an (amide)AeH species, which can form larger aggregates. Increasing the bulk of the amide ligand decreases aggregate size but it is unclear what the true catalyst(s) is (are). DFT calculations suggest that amide bulk also has a noticeable influence on the thermodynamics for formation of the (amide)AeH species. Complex 1-Ba is currently the most powerful Ae metal hydrogenation catalyst. Due to tremendously increased activities in comparison to those of previously reported catalysts, the substrate scope in hydrogenation catalysis could be extended to challenging multi-substituted unactivated alkenes and even to arenes among which benzene.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Alkaline Earth Metals; Alkenes; Aromatic rings; DFT calculations; Hydrogenation